2019
DOI: 10.3389/fnins.2019.00436
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Hyperandrogen During Pregnancy Causes Depression- and Anxiety-Like Behaviors, and Reduced Hippocampal Neurogenesis in Rat Offspring

Abstract: The hippocampus is a region in which neurogenesis persists and retains substantial plasticity throughout lifespan. Accumulating evidences indicate an important role of androgens and androgenic signaling in the regulation of offspring hippocampal neurogenesis and the survival of mature or immature neurons and gliocyte. Hyperandrogenic disorders have been associated with depression and anxiety. Previous studies have found that pregnant hyperandrogenism may increase the susceptibility of the offspring to depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The multi-functional enrichment analysis indicated that the effects of RIB were implicated in the Wnt signaling pathway and TCF7L2. It has been reported that the TCF7L2 is a key transcriptional effector of the Wnt signaling pathway 50 , which is linked to psychiatric diseases and AD 51 , 52 . Based on the metabolite–gene network analysis, RIB induced depressive- and anxiety-like behavior and spatial memory impairment might be mediated by the insulin-POMC-MEK-TCF7L2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-functional enrichment analysis indicated that the effects of RIB were implicated in the Wnt signaling pathway and TCF7L2. It has been reported that the TCF7L2 is a key transcriptional effector of the Wnt signaling pathway 50 , which is linked to psychiatric diseases and AD 51 , 52 . Based on the metabolite–gene network analysis, RIB induced depressive- and anxiety-like behavior and spatial memory impairment might be mediated by the insulin-POMC-MEK-TCF7L2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased Gnrh gene expression as a result of prenatal letrozole treatment in female rats was proved in this study for the rst time. In a similar study, pregnant treatment of letrozole in rats caused depression and anxiety-like behaviors due to decreased neurogenesis in hippocampus (17). Letrozole induced mouse model of PCOS showed increased expression of gonadotropin releasing hormone receptor (Gnrhr) in the pituitary, that was not reversible by utamide treatment (18).…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, given that intrauterine hyperandrogenic environment is a critical etiological agent in neurodevelopmental diseases and also hyperandrogenism status in PCOS women, such studies are very important for evaluating PCOS neuroendocrine and neuro-behavior abnormalities (17). Although in our study addressing to main purpose of assessing neuroendocrine changes speci c to PCOS was not straightforward, but this study is a background for future assessments.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, this study explored the effect of BSTJF on the neurological alteration of female offspring born to PCOS model rats. As the dentate gyrus in the hippocampus has an essential role in spatial behavior [ 72 ] and the depression, anxiety and stereotypical behavior of offspring caused by androgen exposure during pregnancy may also be related to changes in the dentate gyrus [ 73 ], our morphological observation focused only on the dentate gyrus. BSTJF affects the behavior of offspring at 5 weeks of age and these effects disappeared at 13 weeks of age; however, the effects on the expression of hippocampal dendritic spines and related receptor proteins were still present.…”
Section: Discussionmentioning
confidence: 99%